Topic switch models for dialogue management in virtual humans - Zhu, Wenjue; Chowanda, Andry; Valstar, Michel F. (2016)
This paper presents a novel data-driven Topic Switch Model based on a cognitive representation of a limited set of topics that are currently in-focus, which determines what utterances are chosen next. The transition model was statistically learned from a large set of transcribed dyadic interactions. Results show that using our proposed model results in interactions that on average last 2.17 times longer compared to the same system without our model.